Excitation and Ionization of Xenon Atoms in Strong UV Laser Fields (Journal of Atomic and Molecular Sciences, 2017)
Neutral Rydberg state excitation in strong UV laser fields of Xe atoms has been studied and compared with direct ionization. The yields of both strong-field excitation and ionization have been measured as a function of UV laser intensity and ellipticity. The underlying physical mechanism has been discussed based on the experimental results, indicating that the Rydberg states are populated via multi-photon resonance excitation in strong 400 nm laser fields. Finally, a comparative study of Xe and $O_2$ with similar ionization potentials have been performed, showing the suppressed excitation of molecules in strong UV laser fields.
Keywords: Strong UV laser field; Rydberg state excitation; Multi-photon ionization.